Terapia comunitária: bases teóricas e resultados práticos de sua aplicação - Luisi, Liz Verônica Vercillo (2006)
The Community Therapy (TC), created and spread out by it s founder, the Brazilian psychiatrist from Ceará, ADALBERTO BARRETO, is a therapeutic practice that offers community space for the expression of suffering, from personal, social and family conflicts, specially for people of communities characterized for great social inequality; main reason they don t have easy access to mental health services they have the right to. The TC intends to favor the group s own therapeutic dimension, promoting life and the mobilization of resources and personal, family and community abilities. The cultural heritage and the knowledge that comes from daily life is valued, which permits the formation of social solidarity networks. TC has shown as a powerful tool of attendance of great demands in the areas of health and education, especially those involving challenges as violence, alcoholism, substance abuse, mental health problems and many others. Today, all over Brazil, there are more than eight thousand community therapists. The huge interest from different professionals for this formation, plus the strength of the results from its practice was the main reason to choose it as the subject of this thesis. Starting from a pioneer experience in the city of São Paulo, between 2002 and 2003, the interest for this research, besides the possibility to understand the meanings given to the Community Therapy by the people who were part of it, is to built a basic theoretical systematization considering the main concepts involved: community, TC´s theoretical substrata, issues of context (vulnerability and risk), and a clear explanation of the therapeutic practice and it s process. The method used was the qualitative research, with semistructured interviews and, used as reference the narrative approach and the reconstruction of new meanings. Five people were interviewed, and what they said is presented as TC examples that took place at a community in the west part of São Paulo s metropolitan area. The qualitative analysis shows the different meanings given to TC, as great solidarity community mobilization, the ability to deal better with the daily difficulties, easy choice making and better quality at professional relationships